STUDI KINETIKA ADSORPSI Al-MCM 41 TERHADAP METILEN BIRU - Mustofa Ahda; Sutarno Sutarno; Eko Sri Kunarti (Pharmaciana, 2016)
The synthesis and kinetics studies of Al-MCM 41 of the methylene blue adsorption have been done. The observations of the adsorption kinetics are very important parameter in the adsorption process. This is the higher of adsorption kinetics tend to faster adsorption process. The results of characterization of Al-MCM 41 have a wall thickness is 15.173 Å, Pore Volume Pore is 0.584 cm3/g, Pore Diameter is 30.446 Å, Surface Area is 995.513 m2/g. The results of the adsorption kinetics of Al-MCM 41 to methylene blue adsorption follows pseudo second order with coefficient of determination (r2) value of 0.999 and the value of adsorption rate constant of Al-MCM 41 is 10-2 g.mg-1.min-1.